Batik as Social Criticism: The “Justicia” Motif and the Representation of Legal Inequality in Indonesia - Aninda Dyah Hayu Pinasti Putri; Salim; Caesaria Khazena Baria Suryana (PANTUN: Jurnal Ilmiah Seni Budaya, 2026)
Modern batik has evolved beyond its traditional role as decorative textile art and increasingly functions as a medium for cultural reflection and social expression. Previous studies have largely examined batik from aesthetic, historical, and cultural preservation perspectives, while limited attention has been given to its potential as a visual response to contemporary social issues, particularly legal inequality in Indonesia. Addressing this gap, this study aims to analyze the creative process and symbolic meanings embedded in the “Justicia” batik design as a representation of legal disparity in Indonesia. This study employed a qualitative practice-based research approach using Gustami’s artistic creation framework, consisting of exploration, design development, and realization stages. The research process involved identifying issues of legal inequality, collecting visual and textual references, interpreting legal and cultural symbols, and developing motifs and color compositions, while semiotic and visual culture perspectives were applied to interpret the meanings represented in the final work. The findings indicate that the “Justicia” motif reinterprets traditional batik aesthetics into a form of social commentary through symbolic visual elements, including scales of justice, a distorted blade, Javanese script reading "Dewi Zalim" (Tyrannical Goddess), and geometric adaptations of the Slobok motif, which collectively represent unequal law enforcement, structural injustice, and social contradiction. This study demonstrates that contemporary batik can extend its function beyond cultural preservation into a medium of social education and critical reflection and recommends broader exploration of practice-based batik creation as an approach for engaging contemporary societal issues through local cultural expression.